THE EFFECT OF DEFFERENT COLORS OF REARING CONTAINERS ON SURVIVALRATE AND GROWTH OF THE BARRAMUNDI JUVENILE (Latescalcarifer) - Wirasakti, Putra Wirasakti; Diniarti, Nanda; Astriana, Baiq Hilda (Jurnal Perikanan Unram, 2021)
Barramundi (Latescalcarifer) is a variety of fish that spreads over hindia-pacific regions ranging from southeast Asia to Papua New Guinea and northern Australia. The fast demand for national and foreign markets, thus engineered containers of seed cultivation done on land. Color the media becomes a visual influence on fish to acquire food. This, therefore, requires observation on the vessel's color design, which will hopefully improve the growth rate and survival of the Barramundi (Latescalcarifer). The study was carried out for 30 days. It started from August 22 to September 20, 2019. Based on the lombok sea cultivation hall, west septum village, sekotong sub-district, west lombok district, west nusa province. This study is done by experimental methods using a complete random (ral) with four treatments and four deuteronomy, namely, treatment a (transparent/control), b (black), c (blue), and d (green). The anova results indicate the use of a maintenance container of a different color has a real effect on growth, yet it has no real effect on the continuity of life the Barramundi (latescalcarifer). The green container (treatment d) is the best container that has a real effect on LPH weight 2.95 percent, the LPH at 3.84 percent, its absolute weight (bm) 1.35 g.